L’Éloge du doute en Restauration des œuvres d’art - Ségolène Bergeon Langle (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art, 2015)
The doubt is a virtue in preservation-restoration. The author, through examples borrowed from the practice, demonstrates his links with the principle of reversibility, the evolution, the progress and the research.